2005
DOI: 10.1185/030079905x53333
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of the metabolic syndrome using the National Cholesterol Educational Program and International Diabetes Federation definitions

Abstract: MetS could be considered as a 'normal' variant if it was present in the majority of the population. Moreover, the vascular risk associated with IDF-defined MetS could be low, raising cost-effectiveness issues. Alternatively, the new IDF definition may realistically reflect the current MetS epidemic. More studies are required to support or refute those interpretations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
85
3
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(108 citation statements)
references
References 7 publications
13
85
3
7
Order By: Relevance
“…Among the Korean adults in our study, the overall prevalence of the IDF-defined metabolic syndrome was lower than that of the NCEP-defined metabolic syndrome, which appeared to be inconsistent with the studies reported in Greece [15], Australia [16], the US [17] and Mexico [18]. However, the comparison with other studies should be made with caution.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Among the Korean adults in our study, the overall prevalence of the IDF-defined metabolic syndrome was lower than that of the NCEP-defined metabolic syndrome, which appeared to be inconsistent with the studies reported in Greece [15], Australia [16], the US [17] and Mexico [18]. However, the comparison with other studies should be made with caution.…”
Section: Discussioncontrasting
confidence: 54%
“…Hypertension and diabetes were more strongly associated with the NCEP-defined metabolic syndrome in both men and women, whereas coronary heart disease or stroke was more strongly associated with the IDFdefined metabolic syndrome only in women. In the Greek study, the calculated vascular event risk is low in individuals with the IDF-defined metabolic syndrome, compared with those with the NCEP-defined metabolic syndrome [15]. In contrast, in the US study, the participants with hypertension, diabetes, hypercholesterolemia, or coronary heart disease have higher prevalence of the IDF-defined metabolic syndrome than the NCEPdefined metabolic syndrome [17].…”
Section: Discussionmentioning
confidence: 67%
“…In this context, the ATTICA Study, comprising 1,500 women and men from Greece, estimated the prevalence of the metabolic syndrome at 25% in men and 15% in women [14]. Recently, Athyros et al, who considered a Northern Greek population, reported that the ageadjusted prevalence of the NCEP ATP III-defined metabolic syndrome was 25% whereas the IDFdefined prevalence was 43% [15]. Furthermore, the prevalence of the metabolic syndrome in a Portuguese population was 27% in women and 19% in men [16].…”
Section: Epidemiology Of the Metabolic Syndromementioning
confidence: 99%
“…The latter requires abdominal obesity to be present and lowers the diagnostic thresholds for abdominal obesity (26). It is unknown whether the newly included individuals actually share the same cardiovascular risk as the individuals found to be affected by the metabolic syndrome according to the NCEP Adult Treatment Panel III criteria.…”
mentioning
confidence: 99%